PEMANFAATAN PROGRAM WINGEOMPADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN GEOMETRI SISWA - NELLY RHOSYIDA (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract: The progress of science and technology make a positive contribution in education through its products. The use of technology has become a necessity to improve mathematics learning process by providing opportunities for teachers to represent the learning material in a more interesting and varied ways. Studentsâ€™ engagements with, and ownership of, abstract mathematical ideas can be fostered through technology.Teachers already used props and multimedia in geometry learning. Wingeom is one of dynamic geometry software that help students to explore geometry objects easily. The excess of Wingeom in presenting a visualization object geometry is expected to facilitate students' understanding of geometry.Â